(3fcJ GdaJGhi Ydi GdeNJUQGJ GdKdGKI GdJfHjg hGdefgGL hGdMGhjs - (3CMeO Hf YHO GdQMje Hf GdMSjf GdcQOj GdYQGbj, CHh RQYI, hdj GdOjf , GHf GdYQGbj, J (B826 (3g` s
(3ChdgG (B:s
(3GdcdGe Ydi GdHjhY s
(3BNQgG (B:s
(3GdcdGe Yf GdUObGJ s
(3LRA BNQ ef GdfSNI faSgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B148 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B270s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B11 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B489s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ , HgG NQe s
Keywords: (3Gdabg GdTGaYjs